Consolidation of Proceedings at Polish and International Arbitral Institutions - Krawczyk, Gabriela; Piechowiak, Dorota; Przewoźnik, Natalia; Piekutowski, Mikołaj; Rubaszewska, Zuzanna; Frankiewicz, Julia (Polish Review of International and European Law, 2025)
This article examines the procedures for consolidating proceedings in chosen Polish and international arbitration institutions. As Polish arbitration rules of two major institutions recently changed, with new versions of the Rules of the Lewiatan Court of Arbitration (Lewiatan Rules) and, Arbitration Rules of the Court of Arbitration at the Polish Chamber of Commerce (SAKIG Rules) coming into force on 1 January 2025, this paper analyses their implications on dispute resolution efficiency and consistency. Consolidation is highlighted as a critical mechanism for addressing multiple claims related to the same venture, aiding in the prevention of contradictory rulings and reducing costs. A comparative methodology is employed to explore the consolidation frameworks of the SAKIG and Lewiatan Rules. Polish institutions rules on consolidation will be compared with approaches from the International Chamber of Commerce Arbitration Rules (ICC Rules) and the London Court of International Arbitration Rules (LCIA Rules). Key distinctions arise regarding the authority responsible for consolidation, form of party consent, and the compatibility of arbitration agreements. The article discusses the role of the Arbitral Tribunal and the importance of considering the parties’ interests, legal relationships, and procedural efficiency in consolidation decisions. The study reveals a notable shift in the Lewiatan Rules toward a more consensus-driven approach, while the SAKIG Rules show a more gradual and refined development.